Penerapan Promotional Mix Pada Biro Perjalanan Umroh/ Haji Shafira Tour And Travel Surabaya Menurut Perspektif Islam - Kamilina Rhodiyah LD; Fatin Fadhillah Hasib (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
An Increasing number of jama'ah Umrah/Haj in Indonesia every year the show will be the enthusiasm of the congregation to worship in the Holy Land that is not uncommon travel agency action that defraud prospective pilgrims by providing false promotions. This study aims to determine how the promotional mix is right according to Islamic perspective.This study used a qualitative approach with case study method is the shafira Tour and Travel in Surabaya. Data collection techniques is a questionnaires, an interviews and a documentation.Based on the research results, the implementation of sixth promotional mix done by Shafira Tour and Travel compatible with the promotion of the Islamic perspective that is honest, Amanah, does not promote illicit goods and carry out advice based on the results of other studies, congregation only knew four of six promotional mix which is done is through ads, personal selling, sales promotion and WOM.